Atypical employment relationships and commitment: Wishful thinking or HR challenge? - Nicole Torka (Management Revue, 2004)
Nowadays, simultaneously maintaining flexible working practices and commitment is an important topic for HR managers since they both can contribute to organisational success. However, many HRM researchers and practitioners are unsure whether these can go together as job security is often seen as a necessary condition for commitment. Since relatively little research has yet been completed, this article contributes to this discussion. The aim of this article is to explain how flexible workers can be committed. Since knowledge on the matter is very limited, it was decided to conduct an exploratory, qualitative study, observing and listening to welders and fitters in two Dutch companies. The results show that there are more congruencies than differences in terms of commitment between the two groups of workers (typical and atypical). Moreover, the findings also indicate that the commitment of atypical workers depends on a whole range of Human Resource Management choices. HRM for these workers does not begin and end with choices made about human resource flows and specific contract policies. Therefore, an active approach to the whole HRM territory (work systems, rewards, human resource flow, and employee influence) would seem desirable. It was found that all employees want employers to listen to their views regarding policy choices that affect them personally.
Keywords: 650; atypical employment relationships; commitment; HR policies for atypical workers; Personalmanagement; Arbeitsverhältnis